HAKIKAT ANAK DIDIK DALAM PENDIDIKAN ISLAM - Darmiah Darmiah (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2021)
Etymologically, students are students who are taught science. In terminology, students are students or individuals who experience developmental changes so that they still need guidance and direction in shaping their personality and as part of the structural education process. Students are one of the important components in an Islamic education process. Learners are people who take part in the educational process. These people take part in a certain system or type of education to grow and develop themselves. There are also those who define students as people who study in educational institutions, can be referred to as students, students, or students. Formally students are people who are in a phase of growth and development both physically and psychologically, growth and development are characteristics of a participant. students who need guidance from an educator. Growth involves physical, psychological development. Learners seeking the values of life must receive full guidance from educators because according to Islamic teachings when children are born weak and holy/fitrah, the natural surroundings will give color to the values of life. on the religious education of students